When Media Logic Controls Digital Activism: The Escalation of the #IndonesiaGelap Movement on Social Media - Ferdiansyah, Mohamad Tito; Anang Sujoko; Maulina Pia Wulandari (Universitas Brawijaya, 2026)
The development of digital media has transformed political communication, particularly through social media as a space for public mobilization. The #IndonesiaGelap movement exemplifies the escalation of such activism involving students and civil society in response to government policies. While prior studies have examined digital activism, political mediatization, and online participation, they often treat these areas separately, leaving a limited understanding of how media logic shapes communication strategies and movement escalation. This study aims to analyze the role of media logic in digital activism within the framework of political mediatization. A qualitative literature review synthesizes relevant academic works on digital activism, media logic, and political communication to identify recurring patterns. The findings show that digital activism follows media logic through simplified narratives, strong visuals, and strategies oriented toward virality and visibility. More importantly, it reflects a fundamental transformation in how movements are constructed, communicated, and mobilized. This study contributes by positioning media logic as a central lens, offering a more integrated understanding of how digital platforms shape contemporary political participation.